Synergistic Effects of Cabozantinib and EGFR-Specific CAR-NK-92 Cells in Renal Cell Carcinoma - Qing Zhang; Kang Tian; Jinjing Xu; Haixu Zhang; Liantao Li; Qiang Fu; Dafei Chai; Huizhong Li; Junnian Zheng (Journal of Immunology Research)
The chimeric antigen receptor-modified immune effector cell (CAR-T and CAR-NK) therapies are newly developed adoptive treatments of cancers. However, their therapeutic efficacy against solid tumors is limited. Combining CAR-T or CAR-NK cells with chemotherapeutic drugs to treat solid tumor may be a promising strategy. We developed an epidermal growth factor- (EGFR-) specific third-generation CAR. NK-92 cells were modified with the CAR by lentivirus infection. The specific killing ability of the CAR-modified NK-92 cells (CAR-NK-92) against renal cell carcinoma (RCC) cell lines was confirmed in vitro. The synergistic effects of cabozantinib and EGFR-specific CAR-NK-92 cells were investigated in vitro and in vivo. Our results showed that the CAR-NK-92 cells lyse RCC cells in an EGFR-specific manner. Treatment with cabozantinib could increase EGFR and decrease PD-L1 membrane surface expression in RCC cells and enhance the killing ability of CAR-NK-92 cells against the RCC cells in vitro. Furthermore, the CAR-NK-92 cells show synergistic therapeutic efficacy with cabozantinib against human RCC xenograft models. Our results provided the basis for combination with chemotherapy as a novel strategy for enhancing the therapeutic efficacy of CAR-modified immune effector cells for solid tumors.